Creating 'new' commons for the twenty-first century: innovative legal models for 'green space'. Issue 5 (12th May 2018) - Rodgers, Christopher; Mackay, Duncan
Abstract : We all need space; unless we have it, we cannot reach that sense of quiet in which whispers of better things come to us gently. (Hill1883 ) This article considers legal models for creating new commons as a community resource ('green space') in English law. It presents a strategy for creating 'new' commons to 're-purpose' land for public recreation and to (re)-connect people and nature. This will require the creation of common rights – a species of private property right – over private land, to facilitate its registration as common land with open public recreational access. The article considers the types of private property right appropriate and necessary to achieve this overriding purpose, and considers the narratives of locality and identity which this model for 'new commons' could engender. Victorian philanthropists such as Sir Robert Hunter and Octavia Hill led a defensive response to the 'old' enclosure movement. Establishing 'new commons' would, by contrast, start to address some of the concerns raised by the 'new' enclosure movement, by offering a vision for a model of urban common that can provide spaces for human interaction, interdependence and cooperation from which no one is excluded. This would also contribute to addressing key modern public policy objectives for reconnecting people and nature, and contribute to the development of cultural ecosystem services of the kind envisaged by the UK National Ecosystem Assessment and the Biodiversity 2020 strategy for England.